Analisis Kuantitatif Mikroorganisme pada Ragi Tape Lokal dan Daya Terima Tape Jusinta yang dihasilkan - Nurhayani H. Muhiddin; Ramlawati Ramlawati; Nur Arfa Yanti; Abdul Mun'im (University of Halu Oleo, 2019)
The purpose of this study were to analyze the quantity of microorganisms in some local ragi tape and determine the panelists' acceptance of the